Sustained inflammation, coagulation activation and elevated endothelin-1 levels without macrovascular dysfunction at 3 months after COVID-19. Issue 209 (January 2022) - Willems, L.H.; Nagy, M.; ten Cate, H.; Spronk, H.M.H.; Groh, L.A.; Leentjens, J.; Janssen, N.A.F.; Netea, M.G.; Thijssen, D.H.J.; Hannink, G.; van Petersen, A.S.; Warlé, M.C.
Abstract: Introduction: Endothelial damage and thrombosis caused by COVID-19 may imperil cardiovascular health. More than a year since the WHO declared COVID-19 pandemic, information on its effects beyond the acute phase is lacking. We investigate endothelial dysfunction, coagulation and inflammation, 3 months post-COVID-19. Materials and methods: A cohort study was conducted including 203 patients with prior COVID-19. Macrovascular dysfunction was assessed by measuring the carotid artery diameter in response to hand immersion in ice-water. A historic cohort of 312 subjects served as controls. Propensity score matching corrected for baseline differences. Plasma concentrations of endothelin-1 were measured in patients post-COVID-19, during the acute phase, and in matched controls. Coagulation enzyme:inhibitor complexes and inflammatory cytokines were studied. Results and conclusions: The prevalence of macrovascular dysfunction did not differ between the COVID-19 (18.6%) and the historic cohort (22.5%, RD −4%, 95%CI: −15–7, p  = 0.49). Endothelin-1 levels were significantly higher in acute COVID-19 (1.67 ± 0.64 pg/mL) as compared to controls (1.24 ± 0.37, p  < 0.001), and further elevated 3 months post-COVID-19 (2.74 ± 1.81, p  < 0.001). Thrombin:antithrombin(AT) was high in 48.3%. Markers of contact activation were increased in 16–30%. FVIIa:AT (35%) and Von Willebrand Factor:antigen (80.8%) were elevated. Inflammatory cytokine levels were high in a majority: interleukin(IL)-18 (73.9%), IL-6 (47.7%), and IL-1ra (48.9%). At 3 months after acute COVID-19 there was no indication of macrovascular dysfunction; there was evidence, however, of sustained endothelial cell involvement, coagulation activity and inflammation. Our data highlight the importance of further studies on SARS-CoV-2 related vascular inflammation and thrombosis, as well as longer follow-up in recovered patients. Highlights: No indication of macrovascular dysfunction 3 months after acute COVID-19 Elevated ET-1 levels during acute COVID-19, and further elevated after 3 months Increased coagulation activity & high inflammatory cytokines 3 months post-COVID-19